Unexpected Rare Association of Secondary Breast, Thyroid, and Ovarian Lymphomas in a Female Patient with Burkitt Lymphoma: PET-CT Findings - Ouriagli, Salah Nabih (World Journal of Nuclear Medicine, 2022)
We report the case of a 15-year-old female, followed for Burkitt lymphoma with initial ovarian presentation. Positron emission tomography-computed tomography (PET-CT) with 18F-fluorodeoxyglucose (18F-FDG) performed to evaluate initial extension assessment showed an unexpected association with secondary breast, thyroid, and ovarian lymphomas. To our knowledge, this association is very rare, unusual, and these extranodal presentations have been reported in literature as a separate case report. Authors highlight performance of PET-CT with 18F-FDG to determinate the secondary origin of this multiglandular involvement, to establish a lesional map of the whole body, and to contribute to the therapeutic decision.
Keywords: secondary breast; thyroid and ovarian lymphomas; Burkitt lymphoma; PET-CT with 18F-FDG; case report